Energy Relations of Turkey and Azerbaijan. - Momynkulov., Zh. B.; Murtaza., A. Sh. (Journal of Oriental Studies, 2016)
Energy sector is a basis of economic relations of Turkey and Azerbaijan. In this paper we tried to study energy aspects of Turkish-Azerbaijani relations. Despite the existing political controversies, Ankara and Baku, though, promote intense cooperation and close interaction in the energy sector, what had positive impact on the nature of mutual relations. Turkey and Azerbaijan plan to implement beneficial projects like TANAP, BТЕ, Nabucco, TAP, Trans-Caspian pipeline. Strategy of Turkey is to buy energy resources with lower cost and sell them to Europe at preferable higher prices. As for Azerbaijan, it wants to sell its natural gas stocks at acceptable higher prices.